2004
DOI: 10.1210/en.2003-1512
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation and Lack of Secretion of Most Newly Synthesized Proinsulin in Non-β-Cell Lines

Abstract: Myoblasts transfected with HB10D insulin secrete more hormone than those transfected with wild-type insulin, as published previously, indicating that production of wild-type insulin is not efficient in these cells. The ability of non-beta-cells to produce insulin was examined in several cell lines. In clones of neuroendocrine GH(4)C(1) cells stably transfected with proinsulin, two thirds of (35)S-proinsulin was degraded within 3 h of synthesis, whereas (35)S-prolactin was stable. In transiently transfected neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…55 Presumably, beta cells are more optimized than other cells to promote proinsulin folding and solubility, as recombinant proinsulin expression in heterologous cell types is thought to fare worse than endogenous proinsulin expressed in beta cells. 56 Nevertheless, as described throughout this review, beta cells remain quite susceptible to proinsulin misfolding. In the last decade, it has been suggested that a portion of proinsulin in beta cells may be recovered in non-native oligomers or aggregate, the formation of which is susceptible to disturbances in beta cell energy production, calcium changes, reductive stress, and inflammatory cytokine exposure.…”
Section: Misfolded Proinsulin Molecules Occur In Conjunction With Permentioning
confidence: 93%
“…55 Presumably, beta cells are more optimized than other cells to promote proinsulin folding and solubility, as recombinant proinsulin expression in heterologous cell types is thought to fare worse than endogenous proinsulin expressed in beta cells. 56 Nevertheless, as described throughout this review, beta cells remain quite susceptible to proinsulin misfolding. In the last decade, it has been suggested that a portion of proinsulin in beta cells may be recovered in non-native oligomers or aggregate, the formation of which is susceptible to disturbances in beta cell energy production, calcium changes, reductive stress, and inflammatory cytokine exposure.…”
Section: Misfolded Proinsulin Molecules Occur In Conjunction With Permentioning
confidence: 93%
“…However, under condition of physiological pH within the ER, the folding environment seems to be less favorable for proinsulin folding. A study examining stability, secretion and aggregation of wild-type proinsulin in several non-beta cell lines found that none of them could efficiently fold proinsulin (Zhu et al, 2004). In fact, accumulating evidence suggests that, even in normal beta cells, up to 20% of newly synthesized wild-type proinsulin fails to achieve its native folding structure (Liu et al, 2010a; Liu et al, 2005; Wang et al, 2011; Wang and Osei, 2011), suggesting that during biosynthesis, a certain amount of misfolded proinsulin is expected as a by-product.…”
Section: Proinsulin Misfolding In the Ermentioning
confidence: 99%
“…Defining such an “ER proteome” of β‐cell‐specific foldases represents a major goal of current studies. Altered ER proteomes in non‐neurosecretory cell lines is likely to underlie their impaired ability to support the efficient folding and secretion of proinsulin [102].…”
Section: Mechanism Of Disulfide Pairingmentioning
confidence: 99%